THE INFLUENCE OF SCHOOL PRINCIPAL LEADERSHIP, TEACHER WORK MOTIVATION, AND PROFESSIONAL COMPETENCE ON THE QUALITY OF PUBLIC ELEMENTARY SCHOOLS IN BANTARBOLANG DISTRICT - Andi Dwi Arifin; Widya Kusumaningsih; Soedjono Soedjono (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the influence of principal leadership, work motivation, and teachers’ professional competence on the quality of public elementary schools in Bantarbolang District. A quantitative approach with a correlational design was employed. The study population comprised 345 teachers and principals from 46 public elementary schools, with a sample of 185 respondents selected through proportional random sampling. Data were collected using questionnaires that had been tested for validity and reliability. The results indicate that principal leadership has a significant influence on school quality, contributing 54.4%. Teachers’ work motivation also shows a significant impact, contributing 53.9%. Furthermore, teachers’ professional competence contributes 41.5% to school quality. Simultaneously, the three independent variables have a positive and significant effect on school quality, with a total contribution of 75.9%. These findings suggest that improving school quality can be achieved through strengthening principal leadership, enhancing teachers’ work motivation, and developing their professional competence. This research is expected to contribute to efforts in improving the quality of education in elementary schools and serve as a reference for future studies in the field of educational management.